A New Organocatalytic Approach to Substituted Unsaturated Lactams - De Rosa, Margherita; Talotta, Carmen; Soriente, Annunziata (Letters in Organic Chemistry, 2009)
The first organocatalytic approach to erythro and threo lactam derivatives was successfully achieved from the addition of TBSOP (1) to aromatic and aliphatic aldehydes in the presence of a commercially available urea-derivative 5 supporting the broad potential for hydrogen-bond catalysis in the vinylogous Mukaiyama aldol addition. The transition states leading to the major diastereoisomers are discussed.
Keywords: TBSOP